JATROPHA CURCAS PLANT AS A POTENTIAL BIODIESEL FEEDSTOCK IN INDONESIA - Fadjar Goembira; Taufiq Ihsan (Universitas Andalas, 2013)
One of the alternatives for biodiesel feedstock is oil from Jatropha curcas plant. The advantages ofusing this plant are due to its ability to grow in poor soils, different parts of the plant can also be usedfor different purposes, the by products of biodiesel productions have economic values, and biodiesel ismore environmentally friendly when it is being produced and being used, compared to mineral derivedoils. Although Indonesia has another alternative raw material for biodiesel production, i.e. palm oil,however the use of palm oil will affect its supply for the other sectors that have already established,e.g. for producing cooking oils. This situation will not happen to Jatropha curcas oil, due to itsinedible characteristic.Keywords: Biodiesel, Jatropha curcas, Indonesia